Analysis of the Implementation of Electronic Medical Records for Outpatient Registration at Dustira Hospital - Rifky Ahmad Maulana; Yuyun Yunengsih (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2025)
This research is based on the importance of implementing Electronic Medical Records (EMR) in the digitalization of healthcare services, particularly in the outpatient registration process. The purpose of this study is to analyze the implementation of EMR in outpatient registration, examine the role of Medical Recorders, and identify obstacles and possible solutions. The research method used is descriptive with a qualitative approach, which includes direct observation, in-depth interviews, and analysis of SOP documents and flowcharts, as well as a literature review of related scientific journals and books published in the last decade. This literature review is used to strengthen the theoretical basis, compare the results obtained in the field with previous research, and develop a state of the art framework. The results of the study indicate that the EMR system has been connected at all stages of registration, starting from checking patient data, inputting information into the Hospital Management Information System (SIM-RS), to printing the Participant Eligibility Letter (SEP). The role of Medical Recorders is very important in ensuring the smooth registration process and the accuracy of patient data. However, several issues arose during the system's implementation, including technical issues with the SIM-RS, an unstable network, and a lack of technical training for Medical Recorders. Based on the findings, it is recommended to strengthen the technology infrastructure, improve the SIM-RS system, and implement regular training and digital literacy programs for Medical Recorders to support the creation of effective, accurate, and long-term outpatient registration services.